A Study to Assess the Psychosocial Problems and Quality of Life among Transgender in Puducherry (International Journal of Food and Nutritional Sciences, 2022)
Background: Transgender is an umbrella term that describes people whose gender identityor expression does not match the sex they were assigned at birth. Transgender are mostamong the vulnerable and marginalized population in all over the India. Transgender peopleare stigmatised in our society and are being discriminated in every aspect of life. They arefaced with a multitude psychosocial problem it starts from in early childhood and it continuesthroughout their lifespan.Aim: To assess the psychosocial problems and quality of life among transgender.Materials and Methods: A descriptive survey research design was undertaken in SCOHDSociety (Sahodaran community-oriented health development), Puducherry and Pookkalassociation in (Ariyankuppam). Around 215 transgender were selected based on the inclusioncriteria through Non probability convenience sampling technique. Data collection wasperformed based on the interview schedule, demographic variables, DASS 21 scale, & WHOBREF scale. The data was analysed by descriptive and inferential statistics.Result: The present study findings revealed that, relationship between the psychosocialproblems of depression (r=-0.361), anxiety (r=-0.257), stress (r=-0.354) and quality of lifehad a negative correlation, which clearly infers when depression, anxiety and stress levelincrease, the quality of life automatically get decreased. Hence the P value is < 0. 0001. Conclusion: The transgender was exposed to have increased psychosocial problems ofdepression, anxiety and stress, they have a poor quality of life.